THE INFLUENCE OF DIGITAL SECURITY SYSTEM RELIABILITY ON BANK BRI E-BANKING SERVICES - Oktafiana, Lina; Ayu Sifriatul imania; Ani Qotuz Zuhro’ Fitriana (Indragiri Research Center (ingreat), 2025)
This study aims to analyze the influence of digital security systems on the E-Banking services of Bank BRI. The advancement of digital technology facilitates financial transactions but also increases the potential for cybersecurity threats. Using a quantitative approach through the distribution of questionnaires to 30 student users of BRI E-Banking at UIN KHAS Jember, data were obtained regarding their perceptions of security and satisfaction with the BRIMO service. The research results show that the majority of respondents feel safe and satisfied with the implemented E-Banking system, with the percentage of “agree and strongly agree” responses exceeding 75% across various indicators. The validity test of the questionnaire shows that the instrument used is valid and relevant to measure the influence of digital security on e-banking services. This study emphasizes the importance of reliable digital security systems in maintaining customer trust and comfort in conducting electronic transactions.